Designs, Synthesis, Docking Studies, and Biological Evaluation of Novel Berberine Derivatives Targeting Zika Virus. (19th April 2021) - Nguyen, Cuong Quoc; Nguyen, Thi Hong Minh; Nguyen, Thi Thu Thuy; Bui, Thi Buu Hue; Nguyen, Trong Tuan; Huynh, Nhu Thao; Le, Thanh Do; Nguyen, Thi Mai Phuong; Nguyen, Duy Tuan; Nguyen, Minh Tam; Pham, Minh Quan; Tran, Quang De; et al.
Abstract : The World Health Organization has designated Zika virus (ZIKV) as a dangerous, mosquito-borne flaviviral pathogen that was recently found to be responsible for a dramatically increased number of microcephaly cases and other congenital abnormalities in fetuses and newborns. There is neither a vaccine to prevent nor a drug to treat ZIKA virus infections, at the present time. Berberine (BBR) is a promising drug approved by FDA against flaviviral dengue virus, and BBR derivatives are of great interest in antiviral drug development. In this study, we synthesized eight BBR derivatives by introducing benzyl groups at the C-13 position of BBR and converting to respective 8-oxoberberine derivatives, performed molecular docking analysis, and evaluated their anti-Zika virus activity utilizing a cell‐based phenotypic assay. Binding mode analysis, absolute binding free energy calculation, and structure-activity relationship studies of these compounds with ZIKV NS3 receptor were collected. Amongst these studied compounds, compound 4d with a structure of 13-(2, 6-difluoro)-benzylberberine showed high binding affinity (docking score of −7.31 kcal/mol) towards ZIKV NS2B-NS3 protease with critical binding formed within the active site. In the cell-based assay, compound 4d displayed the highest antiviral efficacy against ZIKV with a selective index (SI) of 15.3, with 3.7-fold greater than that of berberine. Together, our study suggests that the potential ZIKV NS2B-NS3 protease inhibitor, compound 4d, is the best alternative to BBR and, further, extends an assuring platform for developing antiviral competitive inhibitors against ZIKV infection.